Sugar Maple, Red Maple, and Yellow Birch Growth and Mortality in Even-Aged Adirondack Northern Hardwoods. Issue 1 (26th September 2020) - Nyland, Ralph D; Bevilacqua, Eddie; Ruff, David A; Kiernan, Diane H
Abstract: Tree diameter growth models for northern hardwoods commonly used large data sets representing a composite of stands with varying management histories, structural characteristics, and age distributions. Yet common predictor variables like diameter can show differences in growth patterns for stands with different age structures and management histories. To address that, we modeled growth and mortality for sugar maple, red maple, and yellow birch in thinned even-aged Adirondack northern hardwoods. Findings indicate that change in diameter depends on initial diameter for sugar maple, with the rate decreasing exponentially from the largest size class to the smallest. Initial diameter did not prove significant with red maple and yellow birch in these thinned stands, perhaps because of the limited sample of trees of small diameter. Stand relative density and time since treatment affected growth for all three species. Those variables also proved significant for predicting mortality of sugar maple. Analyses revealed fewer losses of sugar and red maples among the larger diameter classes, but no relationship with diameter for yellow birch. Plot relative density did not affect mortality with red maple, but time after thinning had a significant effect on survival of all species.